Management of intra-articular fracture of distal femur with LCP and Lag screws in adults - Daroch, Manjit S.; Vashisht, Deepak; Sreen, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Background: Accurate reconstruction of articular surface of distal femur by closed manipulation is not possible. The recent trend for displaced intra-articular fractures of the distal femur is open reduction and stable osteosynthesis with early rehabilitation. The best exposure is achieved through Swashbuckler approach with good results. Purpose of the study was to review the surgical management with LCP and lag screws of complex and most challenging intra-articular fracture of distal femur. Methods: 30 cases of intra-articular fractures of distal femur were treated with LCP and Lag screws in adults. Regular follow-up with all records was carried out for a period of 36 months. Most of patients were treated with Swashbuckler approach. Final outcome was carried based on Neer’s criteria. Results: Union was achieved in all the cases and mean time was 15 weeks. Patients have more range of motion in C1 and C2 types of fracture as compare to C3 Types. Mean range of motion was 1140. Early physiotherapy has big role to achieve good range of motion. Conclusions: LCP is better implant in comminuted I/A fractures of distal end of femur and in elderly patients with osteoporotic bone. In spite of the worst fracture anatomy of the comminuted fracture of distal femur and the poor quality of bone in elderly patients, this can provide better post-operative range of knee motion with overall better Knee score, achieving bony union in all the cases with early physiotherapy.